OCCUPATIONAL STRESS AND JOB PERFORMANCE - Kousar, Sumaira; Dogar, Imtiaz Ahmad; Ghazal, Saima; Khattak, Idrees (Journal of Pakistan Psychiatric Society, 2006)
Objective: The present study was conducted to assess the levels of stress among five different depart-ments of a Multinational Corporation and the effect of stress on employee performance.Design: Cross sectional Survey.Place and duration of study: Workplace of a multinational organization factory located near Faisalabadfrom March 2005 to July 2005.Subjects and Methods: Sample consisted of 65 employees working in 5 different Departments of amultinational organization. Occupational stress scale (OSS) consisting of nine factors contributing tostress was used to assess stress level of workers and its effect on performance was measured by the jobperformance rating scale. One-way Analysis of Variance (ANOVA) was applied to see the difference instress level of workers among five different departments and correlation analysis was done to see therelationship of stress and performance.Results: Results showed that employees in the Human Resource, Productions, Engineering & Refrig-eration, Stores and Electrical & Instrument Departments had moderate levels of stress due to workoverload, co-workers and repetitive work. However there was significant negative correlation betweenworkload and job performance (-0.286; p<0.05). But there was no significant relationship between levelof overall stress and job performance.Conclusion: It was concluded that there was moderate level of stress with no significant difference indifferent departments however no affect of stress was found on job performance.Key words: Occupational stress, Job performance, OSS.